2005
DOI: 10.1074/jbc.m413391200
|View full text |Cite
|
Sign up to set email alerts
|

Nonequivalence of the Nucleotide Binding Domains of the ArsA ATPase

Abstract: The arsRDABC operon of Escherichia coli plasmid R773 encodes the ArsAB pump that catalyzes extrusion of the metalloids As(III) and Sb(III), conferring metalloid resistance. The catalytic subunit, ArsA, is an ATPase with two homologous halves, A1 and A2, connected by a short linker. Each half contains a nucleotide binding domain. The overall rate of ATP hydrolysis is slow in the absence of metalloid and is accelerated by metalloid binding. The results of photolabeling of ArsA with the ATP analogue 8-azidoadenos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2
1

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…Trp-159, which is located near the C-terminal end of STD1, reports slow conformational changes during basal hydrolysis and rapid conformational changes during metalloid-activated ATP hydrolysis (6). This fluorescence enhancement reports predominantly NBD1 activity in both the basal and activated states because NBD1 hydrolyzes ATP considerably faster than NBD2 under both sets of conditions (4). Moreover, the rate of fluorescence enhancement in the unactivated state is equivalent to the steady-state rate of basal hydrolysis (16).…”
Section: Effect Of Elimination Of Mbd Site 1 On Nbd1-mentioning
confidence: 94%
See 2 more Smart Citations
“…Trp-159, which is located near the C-terminal end of STD1, reports slow conformational changes during basal hydrolysis and rapid conformational changes during metalloid-activated ATP hydrolysis (6). This fluorescence enhancement reports predominantly NBD1 activity in both the basal and activated states because NBD1 hydrolyzes ATP considerably faster than NBD2 under both sets of conditions (4). Moreover, the rate of fluorescence enhancement in the unactivated state is equivalent to the steady-state rate of basal hydrolysis (16).…”
Section: Effect Of Elimination Of Mbd Site 1 On Nbd1-mentioning
confidence: 94%
“…2A). Reciprocally, binding of nucleotide is also enhanced by metalloid binding (4). However, it should be pointed out that the concentrations of ADP and ATP in the cytosol of E. coli are sufficient to saturate ArsA at all times, so in vivo binding of metalloid would be independent of nucleotide.…”
Section: Binding Of Sb(iii) Tomentioning
confidence: 99%
See 1 more Smart Citation
“…In the presence of metalloid, ATP hydrolysis is stimulated in both NBD1 and NBD2, with hydrolysis at NBD1 stimulated to a greater degree than at NBD2 (11). These properties suggest that the two NBDs have different properties, and may therefore have different functions.…”
mentioning
confidence: 97%
“…These experiments suggested that the two homologous halves of ArsA are functionally nonequivalent (Jiang et al, 2005 (gray) are shown as space-filling models. A novel metalloid binding domain (MBD) is also located at the A1-A2 interface and is over 20 Å distant from the NBDs.…”
Section: Arsa Atpasementioning
confidence: 99%